WAYS OF IMPROVING THE ADMINISTRATIVE LEGISLATION REGULATING THE PROVISION OF TERRITORIAL DEFENSE BY THE NATIONAL GUARD OF UKRAINE (Bulletin of criminological association of Ukraine, 2024)
It was found that the conceptual principles of ensuring the territorial defense of the National Defense of Ukraine are a system of the most important, fundamental ideas and principles, worldview positions and beliefs that reflect the consolidated position of the authorities and civil society regarding the mission of the National Defense of Ukraine in the field of providing territorial defense, what challenges and problematic issues exist in this area, what are the directions and prospects for overcoming them, as well as improving and developing the mechanism of the researched support. It has been established that an important direction of improving the administrative legislation, which regulates the provision of territorial defense by the National Guard of Ukraine, is the determination of the material, legal and procedural principles of the organization and implementation of the mechanism of interaction of the National Guard of Ukraine with other subjects of public power in the provision of territorial defense. In general, the current state of administrative legislation, which regulates the provision of territorial defense of the NG of Ukraine, should be characterized as requiring further refinement and improvement, in order to ensure its relevance and compliance with the urgent needs of territorial defense. It is emphasized that the steps proposed above do not solve all the existing problems and shortcomings that exist in the administrative and legal basis of the mechanism for providing territorial defense to the National Defense of Ukraine, however, their proper implementation should significantly improve the quality and effectiveness of the mentioned provision.
Keywords: administrative legislation; improvement; territorial defense; National Guard of Ukraine